Antitrust intervention and price transmission in pasta supply chain - Luca Cacchiarelli; Alessandro Sorrentino (Agricultural and Food Economics, 2016)
The issue of price transmission along the food chain has attracted considerable interest in the EU because of the welfare and policy implications that could potentially be generated. Possible consumer welfare loss may exist if price increases are rapidly transmitted through the supply chain, while price decreases are transmitted more slowly, or incompletely. Pasta is a strategic product in the Italian agro-food industry. In the last years, among the events which have characterized the Italian pasta supply chain such as CAP reform and prices instability, a case of anticompetitive practices against pasta makers was identified and sanctioned by the Italian Antitrust Authority for the period between October 2006 and, at least, March 2008. Specifically, based on Antitrust sentence Italian pasta makers (about 90% of Italian market) and two Industrial Unions of Italian pasta makers have put into practice a restrictive-competition accord aimed at harmonizing increases in the sale price for semolina dry pasta that applies to the retail sector. Our goal is to investigate whether antitrust sentence has produced some substantial effects in the Italian pasta market by restoring a state of appreciable competitiveness among companies. A useful way to analyze pasta makers' behavior, before and after antitrust sentence, is to investigate whether and how the mechanism of the transmission price, specifically the pasta producer price adjustment process to semolina price variations, was changed with antitrust intervention. We use Kinnucan and Forker model which has been employed in literature for analyzing the impact of a policy intervention on farm-to-retail price transmission in the fluid milk market. The results showed that antitrust intervention would seem have produced some substantial effects in the Italian pasta market by restoring a state of high competition among companies.
Keywords: 330